Empowerment of the Elderly Through Balance Exercise and Creative Industry Training Using an Occupational Therapy Approach in Solok Regency - Sonya Nelson; Arif Fadli Muchlis; Fahmil Haris; Septri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
An elderly person is defined as someone over the age of 60 who experiences physiological changes and a decline in bodily functions due to aging. The partner for this community service initiative is the Kandung community (*Kenagarian*) in Koto X District, Solok Regency. The issues faced by the partner include: (1) limited knowledge regarding individual potential, independence, and health, alongside a lack of active engagement among the elderly; and (2) employment challenges specifically for those considered "non-productive "where the majority are no longer working despite a continued desire to do so. The lack of productivity among some elderly individuals results in reduced income, potentially leading to poverty. The proposed solution involves creative industry training utilizing an occupational therapy approach specifically, crafting items from recycled materials. The objectives of this activity are to improve the health and productivity of the elderly, foster social interaction among them, and provide meaningful ways to utilize their leisure time. The assistance method employs a "Training of Trainers" (TOT) model, combining lectures with hands-on practical sessions. The outcomes of this initiative include enhanced knowledge and skills regarding balance exercises and handicraft production, as well as increased productivity among the elderly participants.